Re-imagining Paulo Freire through Rortian Neo-Pragmatism - Ramazan Gungor (Adult Education Research Conference, 2012)
Paulo Freire is arguably one of the most well-known educators of our time. Pedagogy of the Oppressed (Freire, 1970) is a very widely read book by an educator in the last century, and is worthy of holding a special place in the history of educational thought (Roberts, 2000). What makes Freire‘s work important is that it does not stand still. It offers itself up to different readings, audiences, and contexts (Giroux in McLaren & Leonard, 1993). This is partially because of the ingenuity of the educators who reinterpreted his work to make it better fit the times and the educational settings in which they were interested as well as the rich, complicated texture of his educational philosophy grounded in the experiences of a practitioner theorist with a very keen eye. Acknowledging the value and continuing usefulness of Freire‘s pedagogy, this paper aims to re-read and re-imagine some of Paulo Freire‘s work (1970, 1998, 2000, 2004, 2005; Freire & Macedo, 1987) using a Rortian1 (1979, 1989, 1991a, 1991b, 1999, 2007) perspective. The center of the analysis, Freire‘s claims about a universal human nature, is relatively narrow so as to have a sharper focus for the study. I argue that Richard Rorty, the late neo-pragmatist philosopher who was admired as well as criticized for his views on traditional philosophical questions, provides an effective set of tools to help us return to Freire‘s conception of a universal human nature. In Rorty‘s writings, I found only one indirect reference to Freire. When he was asked if religion can play a significant role in changing the society for the better, in pragmatist progress, Rorty responded: ―Sometimes it has been useful. ‗Liberation theology‘ was useful in Latin America until the present pope decided to stamp It out.‖ (Rorty & Mendieta, 2006, p. 157). This comment indicates that Rorty was probably aware of Freire‘s work even though I did not find any references to Rorty in Freire‘s writings analyzed for this paper.